A Sensitivity Enhanced MWCNT/PDMS Tactile Sensor Using Micropillars and Low Energy Ar+ Ion Beam Treatment - Syed Azkar Ul Hasan; Youngdo Jung; Seonggi Kim; Cho-Long Jung; Sunjong Oh; Junhee Kim; Hyuneui Lim (Sensors, 2016)
High sensitive flexible and wearable devices which can detect delicate touches have attracted considerable attentions from researchers for various promising applications. This research was aimed at enhancing the sensitivity of a MWCNT/PDMS piezoresistive tactile sensor through modification of its surface texture in the form of micropillars on MWCNT/PDMS film and subsequent low energy Ar+ ion beam treatment of the micropillars. The introduction of straight micropillars on the MWCNT/PDMS surface increased the sensitivity under gentle touch. Low energy ion beam treatment was performed to induce a stiff layer on the exposed surface of the micropillar structured MWCNT/PDMS film. The low energy ion bombardment stabilized the electrical properties of the MWCNT/PDMS surface and tuned the curvature of micropillars according to the treatment conditions. The straight micropillars which were treated by Ar+ ion with an incident angle of 0° demonstrated the enhanced sensitivity under normal pressure and the curved micropillars which were treated with Ar+ ion with an incident angle of 60° differentiated the direction of an applied shear pressure. The ion beam treatment on micropillar structured MWCNT/PDMS tactile sensors can thus be applied to reliable sensing under gentle touch with directional discrimination.